A Descriptive Study of the Development Stage in Producing a Text-to-Speech Nursing English Audio Book - Risa Arroyyani; Maryani Maryani; Pipin Nurhayati (Bajang Institute, 2026)
This study describes the development stage of producing a text-to-speech-based English for Nursing audiobook, to continue previous research of designing situational syllabus conducted within the framework of the ADDIE model. A descriptive qualitative approach is employed in this study, specifically documenting the production process during the development stage. The process involved at this stage consists of drafting and revising the dialogue script, compiling a vocabulary list and functional expressions, audio production using Natural Reader text-to-speech, editing, and presenting the final result. The content of the audiobook is structured based on the target learners' language proficiency at the CEFR Independent User B1 level. The development process for the English for Nursing audiobook resulted in audio files lasting 20–25 minutes for each chapter, with each chapter divided into five sub-sections: Introduction, Reading Text, Dialogue, Simple Expressions and Vocabulary Enrichment, and Exercise.